2020
DOI: 10.1177/1078155220956305
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting same day administration of pegfilgrastim in the age of biosimilars: A review of literature

Abstract: Purpose Since 2018, several pegfilgrastim biosimilars were approved, which may affect insurance reimbursement. Guidelines recommend pegfilgrastim be administered the days following chemotherapy to prevent hematopoietic toxicity. To date, only the reference pegfilgrastim product has an available autoinjector-device. This has contributed to logistical issues in administering biosimilar agents per guideline recommendations. Administration on the same day as chemotherapy may be a potential alternative when logisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 16 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…Although pegfilgrastim should not be administered until the day after chemotherapy according to the FDA-approved regimen, there has been an ongoing interest in evaluating administration on the same day as chemotherapy [ 29 , 30 ]. Logistic concerns (e.g., scheduling and travel) and convenience continue to evoke interest in same-day administration.…”
Section: Discussionmentioning
confidence: 99%
“…Although pegfilgrastim should not be administered until the day after chemotherapy according to the FDA-approved regimen, there has been an ongoing interest in evaluating administration on the same day as chemotherapy [ 29 , 30 ]. Logistic concerns (e.g., scheduling and travel) and convenience continue to evoke interest in same-day administration.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the reportedly increased risk of myelosuppression and FN with same-day filgrastim (unpegylated, short-acting G-CSF) [21], several studies have investigated possible differences in FN prophylaxis and associated outcomes (grade 3/4 CIN, hospitalizations) between next-day administration and the common real-world practice of same-day administration of pegfilgrastim, the pegylated, long-acting form of G-CSF [24,29,30,33]. A recent review suggested that efficacy of same-day pegfilgrastim may be dependent on the chemotherapy regimen administered [20], and a growing body of data shows that same-day pegfilgrastim can be considered for the neutropenia prophylaxis, as acknowledged in the latest NCCN guidelines [1].…”
Section: Discussionmentioning
confidence: 99%
“…The review article used as a reference in the NCCN guidelines summarized the available data qualitatively rather than quantitatively and concluded the benefit of next-day administration despite five of 11 included publications showing lower or comparable rates and duration of neutropenia and/or FN with same-day administration [37]. In contrast, a more recent review acknowledges mixed outcomes with same-day administration (dependent on tumor type and chemotherapy regimen) and suggests that same-day administration was possible based on case-by-case consideration of patient risk factors and chemotherapy regimen [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the most recent iteration (v1.2022), the National Comprehensive Cancer Network (NCCN) hematopoietic growth factor guidelines recommend next-day administration of pegfilgrastim (i.e., US Food and Drug Administration [FDA]–recommended dosing); however, in acknowledgment of the growing body of evidence, the guidelines indicate that same-day administration may be used [ 4 ]. Any use of same-day administration must be weighed against the potential for increased risk of febrile neutropenia [ 16 ]. Because of the COVID-19 pandemic, the option of same-day administration is especially pertinent to minimize additional clinic visits and risks of SARS-CoV-2 exposure.…”
Section: Introductionmentioning
confidence: 99%